Negative electrode material, secondary battery and electric device
By using characteristic porous carbon particles as negative electrode materials, combined with ordered and disordered carbon structures and elements, the problem that the capacity of graphite negative electrode materials is close to the upper limit is solved, and the energy density of secondary batteries is improved and the circulation performance is improved.
Patent Information
- Application Number
- CN202411854068.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The graphite used in existing secondary batteries, as the negative electrode active material, has reached the upper limit, making it difficult to further increase the energy density of secondary batteries.
A porous carbon particles are provided as the negative electrode material. The XRD pattern is characterized by the presence of the first and second diffraction peaks in the range of 10° to 30°. The ratio of the peak intensity of the second diffraction peak to the peak intensity of the first diffraction peak is between 0.8 and 20. Combined with the ordered and disordered carbon structures, elements such as Ti, Si, Zr, Al, Nb, Cr, Sr, Ba or Ca are added in an appropriate amount to form a carbon framework and a surface carbon layer.
By increasing the gram capacity and true density of the negative electrode material, the energy density of the secondary battery is significantly improved, and the circulation and safety performance are improved.
Smart Images

Figure CN119725525A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a negative electrode material, a secondary battery and an electrical device. Background Art
[0002] As a clean energy source, secondary batteries have gradually spread from electronic products to large-scale power-consuming devices such as electric vehicles. Therefore, the energy density of secondary batteries needs to be further improved.
[0003] Due to its advantages of high conductivity and high stability, graphite is currently the main negative electrode active material for secondary batteries. However, the actual gram capacity of graphite currently used as negative electrode active material for secondary batteries is close to its upper limit: the theoretical gram capacity is 372mAh / g, so when graphite is used as a negative electrode active material, its gram capacity is difficult to further increase, resulting in the energy density of secondary batteries with graphite as negative electrode active material being difficult to further increase. Summary of the invention
[0004] The present application provides a negative electrode material, a secondary battery and an electrical device, which are used to improve the energy density of the secondary battery in which the negative electrode material is located by improving the gram capacity and true density of the negative electrode material.
[0005] In a first aspect, an embodiment of the present application provides a negative electrode material, wherein the negative electrode material is porous carbon particles;
[0006] The XRD spectrum of the negative electrode material includes a first diffraction peak and a second diffraction peak located at 10° to 30°, the half-peak width of the first diffraction peak is greater than the half-peak width of the second diffraction peak, and the ratio of the peak intensity of the second diffraction peak to the peak intensity of the first diffraction peak is A, 0.8≤A≤20.
[0007] In one embodiment, the negative electrode material includes a disordered carbon structure and an ordered carbon structure.
[0008] In one embodiment, the Raman spectrum of the negative electrode material includes a D peak and a G peak, and the peak intensity of the D peak is D The peak intensity of the G peak is G Ratio I D / I G Satisfied, 0.30≤I D / I G ≤1.40.
[0009] In one embodiment, in the Raman spectrum of the negative electrode material, the peak intensity of the D peak is D The peak intensity of the G peak is G Ratio I D / I G Satisfied, 0.75≤I D / I G ≤1.15.
[0010] In one embodiment, the element M in the negative electrode material is at least one of Ti, Si, Zr, Al, Nb, Cr, Sr, Ba and Ca;
[0011] Based on the mass of the negative electrode material, the mass content of the element M is m, where m≤6.5%.
[0012] In one embodiment, A≤6.
[0013] In one embodiment, the XRD pattern of the negative electrode material satisfies at least one of the following conditions:
[0014] (1) The half-peak width of the first diffraction peak is 5° to 9°;
[0015] (2) The diffraction angle of the first diffraction peak is 20° to 24°;
[0016] (3) The half-peak width of the second diffraction peak is 0.5° to 1.5°;
[0017] (4) The diffraction angle of the second diffraction peak is 25.9° to 26.9°.
[0018] In one of the embodiments, in the XRD spectrum of the negative electrode material, the half-peak width of the first diffraction peak is 5° to 9°.
[0019] In one of the embodiments, in the XRD spectrum of the negative electrode material, the diffraction angle of the first diffraction peak is 20° to 24°.
[0020] In one embodiment, in the XRD spectrum of the negative electrode material, the half-peak width of the second diffraction peak is 0.5° to 1.5°.
[0021] In one of the embodiments, in the XRD spectrum of the negative electrode material, the diffraction angle of the second diffraction peak is 25.9° to 26.9°.
[0022] In one embodiment, the negative electrode material includes a carbon skeleton and a carbon layer disposed on the surface of the carbon skeleton.
[0023] In one embodiment, the negative electrode material satisfies at least one of the following conditions:
[0024] (1) The pore volume of the negative electrode material is less than or equal to 0.05 cm 3 / g;
[0025] (2) The specific surface area of the negative electrode material is 0.5 to 50 m2 / g;
[0026] (3) The pore volume of the crushed negative electrode material is 0.1 to 0.9 cm 3 / g;
[0027] (4) The specific surface area of the crushed negative electrode material is 150 to 1500 m 2 / g;
[0028] (5) The pore size of the negative electrode material after crushing is 0.3 to 2.0 nm;
[0029] (6) The apparent density of the negative electrode material is 0.5 to 1.7 g / cm 3 .
[0030] In one embodiment, the pore volume of the negative electrode material is less than or equal to 0.05 cm 3 / g;
[0031] In one embodiment, the specific surface area of the negative electrode material is 0.5 to 50 m 2 / g;
[0032] In one embodiment, the pore volume of the crushed negative electrode material is 0.1 to 0.9 cm 3 / g;
[0033] In one embodiment, the specific surface area of the crushed negative electrode material is 150 to 1500 m 2 / g;
[0034] In one embodiment, the pore size of the crushed negative electrode material is 0.3-2.0 nm;
[0035] In one embodiment, the apparent density of the negative electrode material is 0.5 to 1.7 g / cm 3 .
[0036] In one embodiment, the Dv50 of the negative electrode material is 3 to 12 μm.
[0037] In one embodiment, the negative electrode material is obtained by sintering a source of element M under a first temperature in a halogen atmosphere, then cooling the temperature to a second temperature and continuing to sinter.
[0038] In a second aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a current collector and a negative electrode active material attached to at least one side surface of the current collector, wherein:
[0039] The negative electrode active material includes the negative electrode material described in the first aspect and any possible implementation manner.
[0040] In a third aspect, an embodiment of the present application provides an electrical device, including:
[0041] The secondary battery described in the second aspect.
[0042] One or more technical solutions provided in the embodiments of the present application have at least the following beneficial effects:
[0043] In an embodiment of the present application, a negative electrode material is provided in which the ratio A of the diffraction peak intensity of an ordered carbon structure to the diffraction peak intensity of a disordered carbon structure is between 0.8 and 20, so as to increase the gram capacity and true density of the negative electrode material, thereby increasing the energy density of the secondary battery in which the negative electrode material is located.
[0044] Other features and advantages of the present application will be described in the subsequent description, and partly become apparent from the description, or be understood by practicing the present application. The purposes and other advantages of the present application can be realized and obtained by the structures specifically pointed out in the written description, claims, and drawings. It should be understood that the above general description and the detailed description below are only exemplary and explanatory and cannot limit the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0046] Figure 1 The XRD test diagram of Example 2 provided in the embodiments of the present application;
[0047] Figure 2 This is the XRD diagram after fitting processing of the XRD diagram of Example 2 provided in the examples of the present application. DETAILED DESCRIPTION
[0048] In view of the problem of insufficient gram capacity of negative electrode materials, an embodiment of the present application provides a negative electrode material, which is a porous carbon particle, and the XRD (X-ray Diffraction) spectrum of the negative electrode material includes a first diffraction peak and a second diffraction peak located at 10° to 20°, the first diffraction peak corresponding to the disordered carbon structure is a broad peak, and the second diffraction peak corresponding to the ordered carbon structure is a sharp peak, and the peak intensity ratio of the second diffraction peak to the first diffraction peak is 0.8 to 20. The negative electrode material has an appropriate relative content of ordered carbon structure and disordered carbon structure, thereby improving its own true density, thereby effectively improving its gram capacity; therefore, when the negative electrode material is applied to a secondary battery, it can promote the improvement of the energy density of the secondary battery.
[0049] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.
[0050] The terms “first” and “second” in the specification and claims of this application and the above drawings are used to distinguish different objects rather than to describe a specific order.
[0051] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0052] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0053] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0054] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0055] The embodiment of the present application first provides a negative electrode material, which is porous carbon particles. The XRD spectrum of the negative electrode material includes a first diffraction peak and a second diffraction peak, and the first diffraction peak and the second diffraction peak are both located between 10° and 30°.
[0056] The first diffraction peak is a broad peak, and the second diffraction peak is a sharp peak, so the half-peak width of the first diffraction peak is greater than the half-peak width of the second diffraction peak. 1 The half-peak width f of the second diffraction peak 2 The ratio f 1 / f 2 >4.
[0057] Wherein, the ratio A of the peak intensity of the second diffraction peak to the peak intensity of the first diffraction peak satisfies: 0.8≤A≤20.
[0058] Specifically, since the second diffraction peak corresponds to the ordered carbon structure in the negative electrode material, and the first diffraction peak corresponds to the disordered carbon structure in the negative electrode material, when 0.8≤A≤20, the relative content of the ordered carbon structure and the disordered carbon structure in the negative electrode material is appropriate, which can increase the gram capacity of the negative electrode material on the basis of increasing the true density, and effectively improve the cycle performance and safety performance of the secondary battery in which the negative electrode material is located.
[0059] On this basis, the ordered carbon in the negative electrode material is randomly distributed in the disordered carbon, which can further improve the stability of the material's crystal structure, thereby improving the high-rate (for example, 5C) capacity retention rate and low-temperature capacity retention rate of the secondary battery using the negative electrode material.
[0060] The first diffraction peak is: a characteristic peak corresponding to the (002) crystal plane corresponding to the disordered carbon structure. The second diffraction peak is: a characteristic peak corresponding to the (002) crystal plane corresponding to the ordered carbon structure.
[0061] For example, the value of A can be 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.5, 1.7, 1.9, 2.3, 2.8, 3.2, 3.8, 4.2, 4.6, 5.0, 5.5, 5.6, 5.8, 6.0, 7.0, 8.0, 10.0, 12.0, 14.0, 16.0, 18.0, 20.0, or a range consisting of any two of the values. Preferably, A≤6.
[0062] In one embodiment, the XRD spectrum of the negative electrode material may satisfy: the half-peak width of the first diffraction peak is 5° to 9°.
[0063] Illustratively, the half-peak width of the first diffraction peak can be 5°, 6°, 7°, 8°, 9° or a range consisting of any two values therein.
[0064] In one embodiment, the XRD spectrum of the negative electrode material may satisfy: the diffraction angle of the first diffraction peak is 20° to 24°.
[0065] Illustratively, the first derived diffraction angle may be 20.0°, 20.5°, 21.0°, 21.5°, 22.0°, 22.5°, 23.0°, 23.5°, 24.0°, or a range consisting of any two values therein.
[0066] In one embodiment, the XRD spectrum of the negative electrode material may satisfy: the half-peak width of the second diffraction peak is 0.5° to 1.5°.
[0067] Illustratively, the half-peak width of the second diffraction peak may be 0.5°, 0.7°, 0.9°, 1.1°, 1.3°, 1.5°, or a range consisting of any two values therein.
[0068] In one embodiment, the XRD spectrum of the negative electrode material may satisfy: the diffraction angle of the second diffraction peak is 25.9° to 26.9°. For example, the diffraction angle of the second diffraction peak is 26.0°, 26.1°, 26.2°, 26.3°, 26.4°, 26.5°, 26.6°, 26.7°, 26.8°, 26.9° or a range consisting of any two values therein.
[0069] In one embodiment, the peak intensity I of the D peak in the Raman spectrum of the above-mentioned negative electrode material is D The peak intensity of the G peak is G Ratio I D / I G Satisfied, 0.30≤I D / I G ≤1.40.
[0070] The Raman spectrum is obtained by Raman Spectroscopy.
[0071] The D peak is located at 1300 cm in the Raman spectrum. -1 Up to 1400cm -1 The G peak is located at 1530cm in the Raman spectrum. -1 Up to 1630cm -1 characteristic peaks.
[0072] In one embodiment, 0.75≤I D / I G ≤1.15.
[0073] For example, I D / I G The value of can be 0.75, 0.80, 0.83, 0.85, 0.88, 0.90, 0.92, 0.95, 0.97, 1.00, 1.05, 1.08, 1.10, 1.15, or a range consisting of any two values therein.
[0074] In order to further improve the strength of the negative electrode material and avoid the negative electrode material being used in a secondary battery, the lithium storage activity and specific capacity of the negative electrode material are too fast decayed due to mechanical failure. In one embodiment, in addition to the element C, the negative electrode material may also include a small amount of element M. The element M is at least one of Ti, Si, Zr, Al, Nb, Cr, Sr, Ba and Ca.
[0075] Based on the mass of the negative electrode material, the mass content of the element M is m, where m≤6.5%. For example, m can be 0.01%, 0.02%, 0.03%, 0.1%, 0.2%, 0.5%, 1.0%, 1.5%, 1.8%, 2.1%, 2.3%, 2.8%, 3.2%, 3.7%, 4.1%, 4.5%, 4.7%, 5.2%, 6.5%, or a range consisting of any two values thereof.
[0076] The above-mentioned element M is distributed inside the carbon skeleton in the form of small carbide particles.
[0077] Furthermore, the apparent density of the negative electrode material is 0.5 to 1.7 g / cm 3 , when used in secondary batteries, it can provide a large number of active ions (for example, Li + ) storage site.
[0078] To further reduce the amount of SEI film generated to avoid loss of active lithium and reduce the contact area between the electrolyte and the negative electrode material, in one embodiment, the negative electrode material may further include a carbon layer, which may be disposed on the surface of the carbon skeleton.
[0079] Since the carbon layer is located on the surface of the negative electrode material, it can be considered that the carbon layer forms a coating structure on the surface of the carbon skeleton. Therefore, the carbon layer can convert the pores of the porous structure of the carbon layer on the surface of the carbon skeleton into internal pores, thereby reducing the amount of SEI film generated and reducing the contact area between the electrolyte and the negative electrode material.
[0080] It should be understood that the thickness of the carbon layer in the above coating structure on the carbon skeleton surface is not equal everywhere. In addition, the coating area of the above carbon layer on the carbon skeleton surface is at least more than 50%, but there may be no carbon layer in some areas of the carbon skeleton surface.
[0081] In one embodiment, the thickness of the carbon layer is at least 5 nm. For example, the thickness of the carbon layer is 5 to 200 nm.
[0082] Then: In one embodiment, the above negative electrode material satisfies: the pore volume of the negative electrode material is less than or equal to 0.05cm 3 / g.
[0083] In one embodiment, the specific surface area of the negative electrode material is 0.5 to 50 m 2 / g;
[0084] In one embodiment, the pore volume of the crushed negative electrode material is 0.1 to 0.9 cm 3 / g;
[0085] In one embodiment, the above negative electrode material satisfies: the specific surface area of the crushed negative electrode material is 150 to 1500 m 2 / g;
[0086] In one embodiment, the negative electrode material satisfies the following requirement: the pore size of the crushed negative electrode material is 0.3-2.0 nm.
[0087] The crushing of the negative electrode material can be achieved by crushing a small amount of negative electrode material with a grinder.
[0088] Exemplarily, the above negative electrode material satisfies: the pore volume of the negative electrode material is less than or equal to 0.05 cm 3 / g, and the pore volume of the crushed negative electrode material is 0.1-0.9cm 3 / g.
[0089] Exemplarily, the negative electrode material satisfies: the specific surface area of the negative electrode material is 0.5 to 50 m 2 / g, and the specific surface area of the crushed negative electrode material is 150-1500m 2 / g.
[0090] To further improve the packing density of the negative electrode material, in one embodiment, the volume median particle size Dv50 of the negative electrode material is 3 to 12 μm.
[0091] To promote the random distribution of the ordered carbon structure in the disordered carbon structure, in one embodiment, the negative electrode material is obtained by sintering a source of the element M under a first temperature in a halogen atmosphere, then cooling the temperature to a second temperature and continuing to sinter.
[0092] Based on the same inventive concept, the present application embodiment provides a method for preparing the above-mentioned negative electrode material, which comprises the following steps:
[0093] In an inert atmosphere with a halogen atmosphere content greater than or equal to 5 wt %, the halogen atmosphere and the precursor are subjected to an etching reaction under a first temperature condition for 0.5 to 2 hours to generate a first intermediate product.
[0094] After cooling to the second temperature condition, the halogen atmosphere and the first intermediate product are subjected to an etching reaction for 0.5 to 10 hours to obtain a second intermediate product.
[0095] The temperature remains unchanged, and the atmosphere is changed to an inert atmosphere or an inert atmosphere containing hydrogen to further remove impurities, thereby obtaining the negative electrode material. The negative electrode material has a porous structure.
[0096] The precursor includes a source of the aforementioned element M. The source may be a carbide of the element M, for example.
[0097] In one embodiment, the precursor is a source of element M.
[0098] Corresponding to the element M, the source may be, for example, SiC, TiC, ZrC, NbC, Cr 3 C 2 ,BaC 2 , CaC 2 , SrC 2 、Al 4 C 3 、Ti 3 AlC 2 、Ti 2 AlC、Ti 3 AlCN、Nb 2 AlC、Ti 3 C 2 At least one of .
[0099] Specifically, the volume median particle size Dv50 of the precursor is 3 to 12 μm.
[0100] For example, the halogen atmosphere may include, but is not limited to, F 2 , Cl 2 Br 2 ,I 2 , HF, CCl 4 , CHCl 3 , Cl 2 -H 2 , Cl 2 -HCl, HCl.
[0101] The first temperature condition is greater than the second temperature condition. Specifically, the first temperature condition can be selected from: 400-1500°C. The second temperature condition can be selected from: 200-1300°C.
[0102] Furthermore, the negative electrode material may be subjected to a vapor deposition reaction in an inert atmosphere containing an organic gas at a temperature of 400 to 1000° C. to form a carbon layer on the surface of the negative electrode material.
[0103] The organic gas includes at least one of alkanes, alkenes, and alkynes. The content of the organic gas in the inert atmosphere is greater than or equal to 5 wt%.
[0104] Exemplarily, the organic gas includes at least one of methane, ethylene, acetylene and propane.
[0105] Based on the same inventive concept, an embodiment of the present application further provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte.
[0106] The negative electrode sheet includes a current collector and a negative electrode active material attached to at least one side surface of the current collector.
[0107] The negative electrode active material includes the aforementioned negative electrode material.
[0108] In order to increase the compaction density of the negative electrode active material, in one embodiment, the negative electrode active material may further include graphite.
[0109] In one embodiment, the negative active material layer may further include a thickener, which may include but is not limited to sodium carboxymethyl cellulose.
[0110] The negative electrode active material layer may be provided on one surface of the negative electrode current collector in the thickness direction, or may be provided on both surfaces in the thickness direction.
[0111] The surface of the current collector of the negative electrode may include other additional functional layers in addition to the negative electrode active material. In one embodiment, it also includes a conductive coating.
[0112] The conductive coating may be located between the negative electrode active material layer and the surface of the current collector of the negative electrode.
[0113] The conductive coating may be composed of a conductive agent and a negative electrode binder.
[0114] For example, the conductive agent may include, but is not limited to, carbon materials, metals, or conductive polymers. Among them, the carbon material may include at least one of natural graphite, artificial graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The metal may include metal powders or metal fibers of copper, iron, aluminum, etc. The conductive polymer may include a polyphenylene derivative. The negative electrode binder may include, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, or nylon.
[0115] In one embodiment, the negative electrode plate may further include a protective layer, and the protective layer is located on a surface of the negative electrode active material layer facing the air.
[0116] The negative electrode current collector of the present application is not particularly limited as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include a metal foil, a porous metal plate or a composite current collector.
[0117] The metal foil can be copper foil, copper alloy foil, nickel foil, stainless steel foil or titanium foil. The porous metal plate can be nickel foam or copper foam, etc. The composite current collector can include a polymer material base and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be obtained by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0118] The thickness of the negative electrode current collector may be, for example, 4 to 12 μm, and the thickness of the single-sided negative electrode active material layer may be 30 to 200 μm.
[0119] It should be noted that the aforementioned “surface” may be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no particular limitation as long as the purpose of this application can be achieved.
[0120] In one embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.
[0121] The positive electrode current collector may be, for example, a metal foil or a composite current collector, etc. The metal foil may be, for example, an aluminum foil.
[0122] The composite current collector may include a polymer material base layer and a metal material layer located on at least one surface of the polymer material base layer. For example, the material of the metal material layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver or silver alloy. The polymer material base layer may include at least one of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene or polyethylene.
[0123] The positive electrode active material layer contains a positive electrode active material.
[0124] In one embodiment, the positive electrode active material layer may further include a conductive agent and a positive electrode binder. The conductive agent may be of the same type as the conductive agent in the negative electrode active material layer. The positive electrode binder may be of the same type as the negative electrode binder in the negative electrode active material layer.
[0125] In one embodiment, the positive electrode plate may further include a conductive coating disposed between the surface of the positive electrode current collector and the positive electrode active material layer. The conductive coating may be composed of a conductive agent and a binder, for example.
[0126] In one embodiment, the positive electrode sheet may further include a protective layer covering the surface of the positive electrode active material layer.
[0127] The electrolyte may include an organic solvent and an electrolyte salt, which is determined according to active ions in the secondary battery.
[0128] The organic solvent may include at least one of carbonate compounds, carboxylate compounds, ether compounds or other non-aqueous organic solvents. Carbonate compounds may include but are not limited to at least one of linear carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds. The above-mentioned linear carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The above-mentioned cyclic carbonate may include but are not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), n-propyl acetate, tert-butyl acetate, methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), ethyl butyrate (EB), 1,4-butyrolactone (GBL), decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other non-aqueous organic solvents may include but are not limited to at least one of dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE), sulfolane (SF), 1,2-dioxolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0129] Furthermore, the electrolyte may also include additives. The additives may include at least one of the following: negative electrode film-forming additives, positive electrode film-forming additives, or additives capable of improving certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0130] The additives may include, but are not limited to, at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl carbonate (VEC), diethylene sulfate (DTD), propylene sulfate, vinyl sulfite (ES), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), sulfonate cyclic quaternary ammonium salt, succinic anhydride, succinonitrile (SN), adiponitrile (AND), tris(trimethylsilyl) phosphate (TMSP), and tris(trimethylsilyl) borate (TMSB).
[0131] In one embodiment, the secondary battery is a lithium ion battery, and the positive electrode active material may include a lithium transition metal oxide, which may include but is not limited to lithium nickel cobalt manganese oxide (LiNi 0.90 Co 0.05 Mn 0.05 O 2 、LiNi 0.80 Co 0.10 Mn 0.10 O 2 、LiNi 0.60 Co 0.20 Mn 0.20 O 2 、LiNi 0.50 Co 0.20 Mn 0.30 O 2 、LiNi 0.33 Co 0.33 Mn 0.33 O 2 ), at least one of lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide, lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.
[0132] Accordingly, the electrolyte salt in the electrolyte may include a lithium salt. The lithium salt may include, but is not limited to, lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiODFB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2 ), at least one of lithium difluorobis(oxalate) phosphate (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP).
[0133] In one embodiment, the secondary battery is a sodium ion battery, and the positive electrode active material may include at least one of a sodium transition metal oxide, a polyanion compound, and a Prussian blue compound. The sodium transition metal oxide may include Na 1-x Cu h Fe k Mn l M 1 m O 2-y 、Na 0.67 Mn 0.7 Ni z M 2 0.3-z O 2 、Na a Li b Ni c Mn d Fe e O 2 , where M 1 is at least one of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn or Ba, 0<x≤0.33, 0<h≤0.24, 0≤k≤0.32, 0<l≤0.68, 0≤m<0.1, h+k+l+m=1, 0≤y<0.2; M 2 is at least one of Li, Mg, Al, Ca, Ti, Fe, Cu, Zn or Ba, 0<z≤0.1; 0.67<a≤1, 0<b<0.2, 0<c<0.3, 0.67<d+e<0.8, b+c+d+e=1. The polyanionic compound may include but is not limited to: A 1 f M 3 g (PO 4 ) i O j X 1 3-j 、Na n M 4 PO 4 X 2 、Na p M 5 q (SO 4 ) 3 、Na s Mn t Fe 3-t (PO 4 ) 2 (P 2 O 7 ), where A 1H, Li, Na, K or NH 4 At least one of M 3 is at least one of Ti, Cr, Mn, Fe, Co, Ni, V, Cu or Zn, X 1 is at least one of F, Cl or Br, 0<f≤4, 0<g≤2, 1≤i≤3, 0≤j≤2; M 4 is at least one of Mn, Fe, Co, Ni, Cu or Zn, X 2 is at least one of F, Cl or Br, 0<n≤2; M 5 is at least one of Mn, Fe, Co, Ni, Cu or Zn, 0<p≤2, 0<q≤2; 0<s≤4, 0≤t≤3. Prussian blue compounds may include but are not limited to A 2 μm 6 v [M 7 (CN) 6 ] w ·xH 2 O, where A 2 H + NH 4 + , one or more of alkali metal cations and alkaline earth metal cations, M 6 and M 7 Each independently is at least one of transition metal cations, 0<u≤2, 0<v≤1, 0<w≤1, 0<x<6. For example, A 2 H + , Li + 、Na + , K + NH 4 + , Rb + , Cs + 、Fr + 、Be 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ and Ra 2 + At least one of M 6 and M 7 Each is independently a cation of at least one transition metal element selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sn and W. Preferably, A 2 For Li + 、Na + and K + At least one of M 6is a cation of at least one transition metal element selected from the group consisting of Mn, Fe, Co, Ni and Cu, wherein M 7 It is a cation of at least one transition metal element among Mn, Fe, Co, Ni and Cu.
[0134] Accordingly, the electrolyte salt may include a sodium salt, which may include but is not limited to NaPF 6 、NaClO 4 、NaBCl 4 、NaSO 3 CF 3 and Na(CH 3 )C 6 H 4 SO 3 At least one of .
[0135] In one embodiment, the thickness of the positive electrode current collector is 5 to 20 μm, preferably 6 to 18 μm.
[0136] The thickness of the single-sided positive electrode active material layer is 30 to 400 μm.
[0137] In one embodiment, the positive electrode active material layer may be disposed on one surface of the positive electrode current collector in the thickness direction, or may be disposed on both surfaces of the positive electrode current collector in the thickness direction.
[0138] It should be noted that the above-mentioned “surface” may be the entire area of the positive electrode current collector or a partial area of the positive electrode current collector, and the present application has no particular limitation.
[0139] The secondary battery also includes a diaphragm to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge-discharge. The material of the diaphragm may include, but is not limited to, at least one of polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (such as polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid.
[0140] The type of the separator may include at least one of a woven membrane, a nonwoven membrane, a microporous membrane, a composite membrane, a rolled membrane, or a spun membrane.
[0141] The diaphragm may have a porous structure, and the embodiment of the present application does not limit the pore size of the porous structure. For example, the pore size may be 0.01 μm to 1 μm.
[0142] The embodiment of the present application does not limit the thickness of the diaphragm. For example, the thickness of the diaphragm may be 3 μm to 20 μm.
[0143] The secondary battery of the embodiment of the present application may further include an outer package for packaging the positive electrode plate, the separator, the negative electrode plate and the electrolyte, as well as other components of the secondary battery known in the art, and the present application does not limit the above-mentioned other components.
[0144] The outer packaging may be a hard shell, for example, a hard plastic shell, an aluminum shell, a steel shell, etc.
[0145] The outer packaging may also be a soft package. For example, a bag-type soft package. The material of the soft package may be plastic. For example, the plastic may include but is not limited to at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0146] Based on the same inventive concept, an embodiment of the present application provides an electrical device, which includes the aforementioned secondary battery.
[0147] The electrical device may specifically include, but is not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors.
[0148] The following is described in detail by examples and comparative examples:
[0149] The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0150] (I) Test methods and equipment
[0151] (1) Sampling method of negative electrode sheet and negative electrode active material
[0152] The lithium-ion battery discharged at 0.2C to 2.0V was disassembled, the negative electrode sheet was taken out, and it was soaked in dimethyl carbonate (DMC) for 20 minutes, and then rinsed with DMC and acetone in turn. Then the negative electrode sheet was placed in an oven and baked at 80°C for 12 hours to obtain the treated negative electrode sheet sample. The negative electrode sheet samples in the following compaction density PD test of the negative electrode active material layer and the porosity P test of the negative electrode active material layer were sampled using the above method.
[0153] The negative electrode active material layer on the negative electrode sheet was scraped off with a scraper, and the scraped powder was heat treated at 400°C for 4 hours in a tube furnace under argon protection to obtain a negative electrode active material powder sample. The negative electrode active material samples in the following X-ray diffraction (XRD) test; gram capacity and first efficiency test of negative electrode active materials; maximum inscribed circle diameter D test of pores in internal pore structure; pore volume V test of external pore structure; true density ρ test of negative electrode active materials; Dv50 test of negative electrode active materials; specific surface area S test of negative electrode active materials; and elemental analysis test were all sampled using the above method.
[0154] (2) Apparent density test of negative electrode materials
[0155] According to the standard "GB / T 26930.3-2011 Carbon materials for primary aluminum production - Coal tar pitch Part 3: Determination of density - Pycnometer method", the immersion solvent is butanol, and the apparent density of the negative electrode material under test is tested.
[0156] (3) External force crushing method of negative electrode materials
[0157] The negative electrode material was crushed by external force using an IKA grinder (model MultiDrive control MT Package). The specific parameters were as follows: 20 g of negative electrode material powder was taken, the grinding machine speed was 10,000 rpm, and the crushing time was 30 s. After that, the crushed powder was taken out for testing.
[0158] (4) Negative electrode material adsorption test:
[0159] The pore volume of the external pore structure of the negative electrode material is tested by the ASAP2460-physical adsorption analyzer. Specifically, the powder material to be tested is dried and degassed for pretreatment, and then the adsorption amount of the test gas nitrogen under different pressures is tested by the ASAP2460-physical adsorption analyzer, and the adsorption and desorption isotherms are drawn. The shape of the pore is determined according to the shape of the hysteresis loop, and the pore size distribution curve of the micropores is fitted using the DFT model to obtain the pore size and pore volume information of the negative electrode material.
[0160] (5) Dv50 test of negative electrode active materials:
[0161] The negative electrode active material to be tested was taken, and the particle size distribution of the negative electrode active material was measured using a laser particle size analyzer (Malvern, UK, model: Mastersizer 2000E) according to "GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method".
[0162] (6) Specific surface area test of negative electrode active material:
[0163] The negative electrode active material to be tested was dried in a vacuum drying oven and then placed in a sample tube. The specific surface area S of the negative electrode active material to be tested was tested by nitrogen adsorption / desorption method using a specific surface area analyzer (TristarⅡ3020M). The specific test was conducted in accordance with GB / T 19587-2017 Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method.
[0164] (7) Elemental analysis test:
[0165] The mass ratio of the element with the larger relative atomic mass to carbon in the negative electrode material was obtained by using an inductively coupled plasma optical emission spectrometer (ICP-OES). Weigh 0.5 g of the negative electrode active material to be tested, add 10 mL of concentrated HNO 3 The samples are mixed and digested by microwaves. The digested solution is introduced into an inductively coupled photoelectron (ICP) light source. The ICP-OES device detects the content of different elements based on the characteristic radiation energy emitted by the radiation transition when the outer electrons of the gaseous atoms in the sample return from the excited state to the ground state.
[0166] (8) X-ray diffraction (XRD) test:
[0167] The test method of the diffraction peak of the crystal plane of the negative electrode material is as follows: the negative electrode active material graphite is tested by an X-ray powder diffractometer (XRD, instrument model: BrukerD8 ADVANCE), and the target material is Cu Kα; the voltage and current are 40KV / 40mA, the scanning angle range is 5° to 80°, the scanning step length is 0.00836°, and the time for each step is 0.3s. In the XRD spectrum obtained by the test, the disordered carbon characteristic peak (i.e., the first diffraction peak) and the ordered carbon characteristic peak (i.e., the second diffraction peak) are determined, the peak intensity of the disordered carbon characteristic peak and the peak intensity of the ordered carbon characteristic peak are read, and the ratio A of the peak intensity of the ordered carbon characteristic peak to the peak intensity of the disordered carbon characteristic peak is calculated.
[0168] (9) Raman test:
[0169] Raman test method for negative electrode materials: A laser microscopic confocal Raman spectrometer (Raman, HR Evolution, HORIBA Scientific Instrument Division) is used to scan the particles within the area to obtain the D peak and G peak of all particles within the area. The data is processed using LabSpec software to obtain the peak intensities of the D peak and G peak of each particle, which are I D and I G The laser wavelength of the Raman spectrometer can be in the range of 532nm to 785nm. The value of ID / IG in this article is the I / I of all particles measured in this range. D and I G The average value of the ratio. D peak: generally at 1350±50cm -1 Nearby, by the sp 2 Symmetric stretching vibration of carbon atoms caused by radial breathing mode (structural defects); G peak: appears at 1580±50cm cm -1 Nearby, by sp 2 It is caused by the stretching vibration between carbon atoms, which corresponds to the vibration of E2g optical phonon in the center of the Brillouin zone (in-plane vibration of carbon atoms).
[0170] (10) Gram capacity and initial efficiency test of negative electrode active materials:
[0171] The negative electrode active material, binder styrene butadiene rubber and sodium carboxymethyl cellulose (CMC-Na) were mixed in a mass ratio of 97:1.5:1.5, and then deionized water was added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 40wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, and the single-sided coating thickness was 60 microns. The negative electrode was dried at 85°C to obtain a negative electrode sheet. The negative electrode sheet was cut into a disc with a diameter of 14mm and used as a working electrode, a metal lithium sheet was used as a counter electrode, and a polyethylene (PE) film with a thickness of 7μm was used as a diaphragm. After injecting the test electrolyte, it was assembled into a button battery.
[0172] The button cell was charged and discharged in cycles. The button cell was first discharged to 0mV at 0.05C, and then discharged to 20μA at 0mV constant voltage, and the first discharge specific capacity of the button cell was recorded; then the button cell was charged to 2.5V at 0.05C constant current, and the first charge specific capacity of the button cell was recorded. The mass of the negative electrode active material in the negative electrode sheet was calculated based on the coating weight and area of the negative electrode slurry in the above-mentioned electrode sheet preparation process. The first efficiency and gram capacity were calculated by the following expressions:
[0173] First efficiency = first charge specific capacity / first discharge specific capacity × 100%; negative electrode active material gram capacity Q = first charge specific capacity / mass of negative electrode active material, in mAh / g.
[0174] (11) Test energy density
[0175] The energy density is obtained by testing the lithium ion battery prepared by the lithium ion battery preparation method provided in Test Example 1. Five lithium ion batteries are taken from each group of tested lithium ion batteries, and the lithium ion batteries are repeatedly charged and discharged through the following steps, and the discharge capacity retention rate of the lithium ion batteries is calculated.
[0176] The first charge and discharge were carried out in an environment of 25°C, constant current charging was carried out at a charging current of 1C until the charging cut-off voltage was reached, and then constant current discharge was carried out at a discharge current of 1C until the discharge cut-off voltage was reached, and the discharge capacity of the first cycle was recorded; then 800 charge and discharge cycles were carried out, and the discharge capacity of the 800th cycle was recorded. The charging cut-off voltage of the lithium-ion battery using the negative electrode active material in this application is 4.53V, and the discharge cut-off voltage is 2.0V.
[0177] The cycle performance is calculated by the following expression:
[0178] Cycle capacity retention rate (%) = (discharge capacity at the 1000th cycle / discharge capacity at the first cycle) × 100%.
[0179] Cycle expansion ratio (%) = (thickness of the lithium-ion battery at the 1000th cycle / thickness of the lithium-ion battery at the first cycle) × 100%.
[0180] (12) Test rate discharge capacity retention rate:
[0181] Take 5 lithium-ion batteries from each group and perform the first charge and discharge in an environment of 25°C. Perform constant current at a charging current of 0.2C until the charging cut-off voltage is 4.53V. Then, perform constant voltage charging to 0.02C at the charging cut-off voltage, and then perform constant current discharge at a discharge current of 0.2C to a discharge cut-off voltage of 2.0V to obtain the 0.2C average discharge capacity of the lithium-ion battery. Repeat the above charging process, and then perform constant current discharge at a discharge current of 5C to the discharge cut-off voltage to obtain the 5C average discharge capacity of the lithium-ion battery.
[0182] The rate discharge capacity retention rate is calculated by the following expression:
[0183] 5C discharge capacity retention rate = (5C average discharge capacity / 0.2C average discharge capacity) × 100%
[0184] (12) Test low temperature capacity retention rate
[0185] Take 5 lithium-ion batteries from each group and perform the first charge and discharge in an environment of 25°C. Perform constant current at a charging current of 0.2C until the charging cutoff voltage is 4.53V, then charge at a constant voltage to 0.02C at the charging cutoff voltage, and then discharge at a constant current to a discharge cutoff voltage of 2.0V at a discharge current of 0.2C to obtain the average discharge capacity of the lithium-ion battery at 25°C at 0.2C. Perform constant current at a charging current of 0.2C until the charging cutoff voltage, then charge at a constant voltage to 0.02C at the charging cutoff voltage, then lower the ambient temperature to -20°C and let it stand for 3h. In an environment of -20°C, discharge at a constant current to the discharge cutoff voltage at a discharge current of 0.2C to obtain the average discharge capacity of the lithium-ion battery at -20°C at 0.2C.
[0186] The low temperature capacity retention rate is calculated according to the following expression:
[0187] Low temperature capacity preservation rate = (average discharge capacity at -20°C / average discharge capacity at 25°C) × 100%.
[0188] (II) Preparation
[0189] Example 1
[0190] <Preparation of negative electrode materials>
[0191] S1, 20g of SiC (D v 50=13μm) powder is placed in a rotary furnace and heated to 900℃ (first temperature condition) under a nitrogen atmosphere, and then kept warm. Under the first temperature condition, a chlorine-argon mixed atmosphere with a chlorine content of 50wt% is introduced for etching for 3h (first time). Then the temperature is lowered to 750℃ (second temperature condition), and a chlorine atmosphere is introduced for etching for 10h (second time) under the second temperature condition. Then, still under the second temperature condition, a hydrogen and argon mixed gas with a hydrogen content of 5wt% is introduced for 5h to further remove impurities, and finally the temperature is lowered in a nitrogen atmosphere to obtain a negative electrode material.
[0192] S2. Place the negative electrode material in a rotary furnace, heat it to 850°C (the third temperature condition) in a nitrogen atmosphere for insulation, introduce a mixed atmosphere of methane and argon with a methane content of 20wt% at 850°C for 6 hours, and finally cool it down in a nitrogen atmosphere to obtain a negative electrode material containing a carbon layer.
[0193] <Preparation of lithium-ion batteries>
[0194] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain the electrode assembly. After welding the pole ear, the electrode assembly is placed in an aluminum-plastic film packaging bag, placed in an 80°C vacuum oven to dry for 12 hours to remove moisture, and the above-prepared electrolyte is injected. After vacuum packaging, standing, formation, degassing, trimming and other processes, a lithium-ion battery is obtained. The design potential range of the lithium-ion battery is 2.0~4.53V.
[0195] The above-mentioned negative electrode sheet is prepared according to the following method: negative electrode active material negative electrode material, binder styrene butadiene rubber and sodium carboxymethyl cellulose (CMC-Na) are mixed in a mass ratio of 97:1.5:1.5, and then deionized water is added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 40wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 85°C to obtain a negative electrode sheet with a single-sided negative electrode active material layer coated with a negative electrode active material layer with a thickness of 80μm. Repeat the above steps on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet with a double-sided negative electrode active material layer coated. After cold pressing, cutting and slitting, the negative electrode sheet is obtained.
[0196] The above-mentioned positive electrode sheet is prepared according to the following method: the positive electrode active material lithium cobalt oxide, conductive carbon black (SuperP), and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) is added as a solvent and stirred evenly, and a positive electrode slurry with a solid content of 72wt% is prepared. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 85°C to obtain a positive electrode sheet coated with a single-sided positive electrode active material layer; the above steps are repeated on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a double-sided positive electrode active material layer. Then, after cold pressing, cutting, and slitting, the positive electrode sheet is obtained, and the positive and negative electrode N / P ratio is set to 1.0, that is, the ratio of the negative electrode capacity per unit area to the positive electrode capacity per unit area is 1.0.
[0197] The electrolyte was prepared by the following method: in a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) were mixed in a mass ratio of 1:1:1 to obtain an organic solvent; lithium salt LiPF 6 Dissolve in the above organic solvent, add fluoroethylene carbonate (FEC), mix well to obtain electrolyte. Based on the total mass of the electrolyte, LiPF 6 The mass percentage of is 12.5%, the mass percentage of FEC is 5%, and the balance is organic solvent.
[0198] The above-mentioned separator uses a polyethylene (PE) film with a thickness of 7 μm as the separator.
[0199] Example 2
[0200] The steps and parameters are the same as those of Example 1, except that the first temperature condition in step S1 is different; the first temperature condition is 950°C.
[0201] The XRD test pattern of Example 2 is as follows: Figure 1 In order to accurately determine the ratio A of the peak intensity of the second diffraction peak to the peak intensity of the first diffraction peak in the XRD, Figure 1 Perform fitting processing and obtain Figure 2 .
[0202] Example 3
[0203] The steps and parameters are the same as those in Example 1, except that the first temperature condition in step S1 is different; the first temperature condition is 1000°C.
[0204] Example 4
[0205] The steps and parameters are the same as those in Example 1, except that the first temperature condition in step S1 is different; the first temperature condition is 1100°C.
[0206] Example 5
[0207] The steps and parameters are the same as those of Example 1, except that the first temperature condition of step S1 is different; the first temperature condition is 1200°C.
[0208] Example 6
[0209] The steps and parameters are the same as those in Example 1, except that in step S1, the first temperature condition is 700°C, the second temperature condition is 700°C, and the second time is 24 hours.
[0210] Example 7
[0211] The steps and parameters are the same as those in Example 1, except that the second time of step S1 is different; the second time is 20 hours.
[0212] Example 8
[0213] The steps and parameters are the same as those of Example 1, except that the second time of step S1 is different; the second time is 7 hours.
[0214] Example 9
[0215] The steps and parameters are the same as those of Example 1, except that the second time of step S1 is different; the second time is 5 hours.
[0216] Example 10
[0217] The steps and parameters are the same as those of Example 1, except that the second time of step S1 is different; the second time is 3 hours.
[0218] Embodiment 11
[0219] The steps and parameters are the same as those in Example 1, except that the second time of step S1 is different; the second time is 2.5 hours.
[0220] Embodiment 11
[0221] The steps and parameters are the same as those in Example 1, except that the second time of step S1 is different; the second time is 2.5 hours.
[0222] Example 12
[0223] The steps and parameters are the same as those in Example 1, except that in step S1: SiC is replaced by TiC powder (Dv5013μm), the first temperature condition is changed to 600°C, the first time is 1.5 hours, the second temperature condition is 500°C, and the second time is 10 hours.
[0224] Embodiment 13
[0225] The steps and parameters are the same as those in Example 1, except that in step S1, SiC is replaced by ZrC powder (D v 5013μm), the first temperature condition was changed to 700℃, the first time was 2 hours, the second temperature condition was 400℃, and the second time was 10 hours.
[0226] Comparative Example 1
[0227] The preparation steps S1-S2 provided in Example 1 are not adopted, and the lithium-ion battery is prepared directly using graphite as the negative electrode active material.
[0228] The N / P ratio of the positive and negative electrodes in the lithium-ion battery is set to 1.04, and the potential range is adjusted to 3.0V to 4.48V (ie, the charge cut-off voltage is adjusted to 4.48V, and the discharge cut-off voltage is adjusted to 3.0V).
[0229] Comparative Example 2
[0230] The steps and parameters are the same as those in Example 1, except that the first temperature condition in step S1 is different; the first temperature condition is 1600°C.
[0231] Comparative Example 3
[0232] The steps and parameters are the same as those in Example 1, except that in step S1 the first temperature condition is 400° C., the first heat treatment time is 1.5 hours, the second heat treatment temperature is 500° C., and the second heat treatment time is 24 hours.
[0233] The peak intensity ratio A in XRD and I in Raman spectrum obtained from the tests of various embodiments and comparative examples are as follows: D / I G , element M and its content m, apparent density, pore size, pore volume, specific surface area, D v 50See Table 1 below.
[0234] Table 1
[0235]
[0236]
[0237] The gram capacity, first coulombic efficiency ICE, energy density ratio to comparative example 1, capacity retention rate after 1000 cycles, expansion rate after 1000 cycles, 5C rate discharge capacity retention rate, and low temperature capacity retention rate obtained by testing each embodiment and comparative example are shown in Table 2 below.
[0238] Table 2
[0239]
[0240] It can be seen from Tables 1 and 2 that when the peak intensity ratio A of the second diffraction peak to the first diffraction peak in the XRD spectrum is between 0.8 and 20, its gram capacity is improved, and its cycle performance is also improved.
[0241] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.
Claims
1. A negative electrode material, characterized in that: The negative electrode material is porous carbon particles; wherein, The XRD spectrum of the negative electrode material includes a first diffraction peak and a second diffraction peak located at 10° to 30°, the half-peak width of the first diffraction peak is greater than the half-peak width of the second diffraction peak, and the ratio of the peak intensity of the second diffraction peak to the peak intensity of the first diffraction peak is A, 0.8≤A≤20.
2. The negative electrode material according to claim 1, characterized in that The Raman spectrum of the negative electrode material includes a D peak and a G peak, and the peak intensity of the D peak is D The peak intensity of the G peak is G Ratio I D / I G Satisfied, 0.30≤I D / I G ≤1.
40.
3. The negative electrode material according to claim 1, characterized in that In the Raman spectrum of the negative electrode material, the peak intensity of the D peak is D The peak intensity of the G peak is G Ratio I D / I G Satisfied, 0.75≤I D / I G ≤1.
15.
4. A negative electrode material according to claim 1, characterized in that: The element M in the negative electrode material is at least one of Ti, Si, Zr, Al, Nb, Cr, Sr, Ba and Ca; Based on the mass of the negative electrode material, the mass content of the element M is m, where m≤6.5%.
5. The negative electrode material according to any one of claims 1 to 4, characterized in that A≤6。 6. The negative electrode material according to claim 1, characterized in that The XRD pattern of the negative electrode material satisfies at least one of the following conditions: (1) The half-peak width of the first diffraction peak is 5° to 9°; (2) The diffraction angle of the first diffraction peak is 20° to 24°; (3) The half-peak width of the second diffraction peak is 0.5° to 1.5°; (4) The diffraction angle of the second diffraction peak is 25.9° to 26.9°.
7. The negative electrode material according to claim 1, characterized in that The negative electrode material includes a porous carbon skeleton and a carbon layer arranged on the surface of the carbon skeleton.
8. The negative electrode material according to any one of claims 1 to 4 and 6 to 7, characterized in that The negative electrode material satisfies at least one of the following conditions: (1) The pore volume of the negative electrode material is less than or equal to 0.05 cm 3 / g; (2) The specific surface area of the negative electrode material is 0.5 to 50 m 2 / g; (3) The pore volume of the crushed negative electrode material is 0.1 to 0.9 cm 3 / g; (4) The specific surface area of the crushed negative electrode material is 150 to 1500 m 2 / g; (5) The pore size of the negative electrode material after crushing is 0.3 to 2.0 nm; (6) The apparent density of the negative electrode material is 0.5 to 1.7 g / cm 3 .
9. A secondary battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a current collector and a negative electrode active material attached to at least one side surface of the current collector, wherein: The negative electrode active material comprises the negative electrode material according to any one of claims 1 to 8.
10. An electrical device, characterized in that: include: The secondary battery according to claim 9.
Citation Information
Patent Citations
Hard carbon material, negative pole piece, secondary battery and electric device
CN118125415A
Porous carbon for negative electrode material and composite material for lithium ion secondary battery
CN118630137A
Negative active material, negative plate and battery
CN119108535A